1998
DOI: 10.1111/j.1558-5646.1998.tb01640.x
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC DETERMINANTS OF PROTANDRIC SEX IN THE PACIFIC OYSTER,CRASSOSTREA GIGASTHUNBERG

Abstract: A unique feature of sex in Crassostrea oysters is the coexistence of protandric sex change, dioecy, and hermaphroditism. To determine whether such a system is genetically controlled, we analyzed sex ratios in 86 pair-mated families of the Pacific oyster, Crassostrea gigas Thunberg. The overall female ratios of one-, two-, and three-year-old oysters were 37%, 55%, and 75%, respectively, suggesting that a significant proportion of oysters matured first as males and changed to females in later years. Detailed ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 18 publications
4
58
0
2
Order By: Relevance
“…This observation agrees with a previous study of eastern oysters (Needler 1941), and another for Pacific oysters (Lango-Reynoso, Chavez-Villaba & Le Pennec 2006). It has been suggested that sex change may be under some genetic control in the eastern oyster (Haley 1977) and the Pacific oyster (Guo et al 1998). However, no detailed evidence has been reported to show that sex change is controlled by specific factors (e.g.…”
Section: Sex Reversal Of Oysters Was Bidirectional and Was Not Relatesupporting
confidence: 92%
See 1 more Smart Citation
“…This observation agrees with a previous study of eastern oysters (Needler 1941), and another for Pacific oysters (Lango-Reynoso, Chavez-Villaba & Le Pennec 2006). It has been suggested that sex change may be under some genetic control in the eastern oyster (Haley 1977) and the Pacific oyster (Guo et al 1998). However, no detailed evidence has been reported to show that sex change is controlled by specific factors (e.g.…”
Section: Sex Reversal Of Oysters Was Bidirectional and Was Not Relatesupporting
confidence: 92%
“…In nature, self-fertilization in hermaphrodites is usually avoided through strategies such as asynchronous maturation or outcrossing (Foighil & Eernisse 1987;Rios, Canales & Pena 1996). Due to the free dispersal of gametes, however, most benthic marine invertebrates such as bivalves usually possess a small chance of self-fertilization In oysters of the genus of Crassostrea, hermaphrodites are rare, and occurrence varies with age and environment (Galtsoff 1964;Kennedy, Newell & Eble 1996;Guo, Hedgecock, Hershberger, Cooper & Allen 1998). Therefore, it is not practical to create selfing inbred lines by using natural hermaphrodites.…”
Section: Discussionmentioning
confidence: 99%
“…Sex of individual oysters may be, to a lesser or greater degree, under genetic rather than environmental control, yet environmental factors clearly play a role in genetic expression and generation of hormonal cues (Guo et al 1998, Baghurst & Mitchell 2002. By manipulating environmental factors such as feed availability and temperature during conditioning, hatcheries may be able to select expression of desired sex in some species of bivalve molluscs.…”
Section: Feed Affects Sex Ratiosmentioning
confidence: 97%
“…As S. glomerata exhibits protandric diocey (Asif 1979;Guo et al 1998), it remains unclear whether intersex individuals observed in our initial experiments were functionally intersex or the result of an opportunistic sampling of individuals that were in the process of undergoing an estrogenically mediated protandric transition from male to female. If the latter is the case, we may expect to observe Effects of 17a-ethynylestradiol exposure in the Sydney rock oyster 1441 shifts in the sex ratio towards females with greater exposure durations to estrogens, at later intervals in the gonadal development cycle and/or with greater sampling frequency during such potential transitions.…”
Section: Introductionmentioning
confidence: 98%